Efeitos do tratamento de maloclusão de classe II divisão 1 utilizando aparelho extrabucal com diferentes tipos de tração - Vargas, Diogo Antunes (2014)
The aim of this study was to verify the effects of the headgear (HG) with low traction and high traction on the upper molars, maxilla, mandible and maxillomandibular anteroposterior relationship, as the first step of treatment of Class II malocclusion. The sample comprised of 110 radiographies of 55 patients, 10.3 mean age, divided into 2 groups: Group 1 (n= 37), HG low traction; Grup 2 (n=18), HG high traction. Each group patients were treated until a Class I molar relationship were reached. The results showed distal displacement of molars in Group1 (P< 0,001), with higher distal inclination in Group 1 (P< 0,001). Significant extrusion in the molars (P< 0,001) with clockwise rotation of palatal plane (P< 0,05) in Group 1. In Group 2 no estatistical differences were showed in the molars position. No difference was observed in the anterior positioning of maxilla in both groups.Mandibular forward growth was observed in both groups but more mandibular forward group between T1 and T2 in Group 1(P<0,001) and wtih significant difference between the groups (P>0,05). Maxillomandibular improvement was not significant. Mandibular clockwise rotation was not significant. Considering results, it is possible to conclude, that both treatment was efficient, with more significant results in Group 1, but also with more dental collateral effects